Correlates of ecological dominance within Pheidole ants (Hymenoptera: Formicidae). (29th October 2018) - Tschá, Marcel K.; Pie, Marcio R.
Abstract : 1. In any group of organisms, one can almost invariably find some species that are ecologically dominant (i.e. disproportionately more abundant and widespread), whereas others are comparatively less prevalent. Understanding of the causes of variation in ecological dominance has been elusive, particularly given that dominant and subordinate species often lack obvious features that could predict their abundance in nature. 2. In this study, physiological, behavioural, morphological, and phylogenetic information is integrated in an effort to understand the mechanisms underlying ecological dominance in ants using the hyperdiverse ant genus Pheidole (Formicidae: Myrmicinae) as a model system. Field estimates of the relative abundance of 10 Pheidole species were compared with potential correlates, which included behavioural (walking velocity), physiological (tolerance to high and low temperatures and desiccation), and morphological traits (body size and degree of dimorphism in the worker caste). A molecular phylogeny of the tested species was also generated to account for potential confounding effects of phylogenetic non‐independence. 3. Dominant Pheidole species were characterised by higher environmental tolerance with respect to temperature and humidity, as well as faster walking speeds. On the other hand, no morphological correlates of ecological dominance were detected. Interestingly, subordinate species showed no evidence of trade‐off in performance, being both more fragile to environmental challenges and slower in their walking speeds. 4. These results provide important insights into the mechanisms involved in local species coexistence in Pheidole . Abstract : Physiological, behavioural, morphological, and phylogenetic information are integrated in an effort to understand the mechanisms underlying ecological dominance in ants using the hyperdiverse ant genus Pheidole as a model system. Dominant species were characterised by higher environmental tolerance, as well as faster walking speeds. On the other hand, no morphological correlates of ecological dominance were detected. Subordinate species showed no evidence of trade‐off in performance, being both more fragile to environmental challenges and slower in their walking speeds.